(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the formation process of the gold market, its current state, and future development prospects. The main objective of the study is to identify key trends emerging in the course of the comprehensive reform of the national gold market, examine existing challenges through a systematic approach, and develop scientifically grounded proposals and recommendations to address them.